1990
DOI: 10.1111/j.1432-1033.1990.tb19113.x
|View full text |Cite
|
Sign up to set email alerts
|

Subcellular distribution of lipoxygenase products in rabbit reticulocyte membranes*

Abstract: Mitochondria1 membranes and plasma membranes of rabbit reticulocytes contain oxygenated polyenoic fatty acids such as (9Z,1 1E)-(l3S)-13-hydroxy-9,1l-octadecadienoic acid, 9 s and 9R isomers of (IOE,12Z)-9-hydroxy-10,12-octadecadienoic acid and their all-E isomers. Furthermore (5Z,8Z,112,13E)-(1 5S)-15-hydroxy-5,8,11,13-icosatetraenoic acid, 9-and 13-oxooctadecadienoic acid were detected as minor products. The chemical structure of these products has been identified by co-chromatography with authentic standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 36 publications
0
35
0
Order By: Relevance
“…In addition, these data document changes in membrane composition that occur due to 15-lipoxygenase. While the significance of the observed membrane remodeling is not entirely clear, it has been shown that exogenous 15-HETE can be reincorporated into the membrane (20,21) in such a way that it structurally alters the second messenger diacylglycerol, which is released during cell signaling (21). Alternatively, mammalian 15-lipoxygenases are capable of directly oxygenating phospholipids (22) and biomembranes (3). This oxygenation of membrane lipids is proposed to initiate the degradation of intracellular organelles during red-cell maturation (23,24).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, these data document changes in membrane composition that occur due to 15-lipoxygenase. While the significance of the observed membrane remodeling is not entirely clear, it has been shown that exogenous 15-HETE can be reincorporated into the membrane (20,21) in such a way that it structurally alters the second messenger diacylglycerol, which is released during cell signaling (21). Alternatively, mammalian 15-lipoxygenases are capable of directly oxygenating phospholipids (22) and biomembranes (3). This oxygenation of membrane lipids is proposed to initiate the degradation of intracellular organelles during red-cell maturation (23,24).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, mammalian 15-lipoxygenases are capable of directly oxygenating phospholipids (22) and biomembranes (3). This oxygenation of membrane lipids is proposed to initiate the degradation of intracellular organelles during red-cell maturation (23,24). Hence monocyte 15-lipoxygenase may be recruited to degrade intracellular organelles during differentiation or to digest extracellular particles during phagocytosis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32) The presence of KODE in plant tissues was reported in Arabidopsis 33) and the soybean (Glycine max). 34) KODEs can be produced directly and efficiently by purified lipoxygenases, 35,36) but the enzymatic dehydroge- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The free fatty aCIds were separated from the esterified fatty aCIds on octadecyl-SPE columns accordmg to Kiihn [21], then the absorbances of the fractions were recorded at 205 nm and 235 nm on a Hewlett Packard 8450A double-beam diode array spectrophotometer. The oxidative modification of the membrane lipid fractIOn was expressed by means of the oxidative mdex, I.e.…”
Section: Ssdiooi4-5793(95)00s76-4 ] 4 Membrane Isolation and Spectromentioning
confidence: 99%